The problem in the insertion of Coronavac and Astrazeneca vaccines in the fight against COVID-19 in Brazil (Research, Society and Development, 2022)
This study aims to: to identify modulating factors for insertion of CoronaVac and AstraZeneca vaccines carried out in Brazil. Method: integrative Review, PICo strategy and procedures defined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) for the following guiding question: What challenges were faced for the insertion of COVID-19 vaccines in Brazil. Language of studies: Portuguese. Results: We understand that the main problems faced in inserting the CoronaVac and AstraZeneca vaccines in the initial immunization against COVID-19 in Brazil were: the difficulty in carrying out a safe, fast and economical transport of the vaccine and the planning of a vaccination strategy in large scale. Conclusion: We identified that the difficulty in logistics, maintenance of vaccines and the separation of priority groups were conclusive factors of problematization in the insertion of these vaccines in the emergency context of the pandemic in Brazil.